Economic Analysis of Women Entrepreneurship in Jajarkot District, Nepal - Shahi, Nem Bahadur (Journal of Gurubaba, 2024)
Women entrepreneurship plays a pivotal role in fostering inclusive economic development, especially in rural and underdeveloped regions like Jajarkot district in Nepal. Despite facing significant socio-economic and cultural constraints, women in Jajarkot are gradually engaging in entrepreneurial activities, contributing to household income, local employment, and community welfare. This study aims to analyze the economic dimensions of women entrepreneurship in Jajarkot, focusing on the nature, scope, and outcomes of their entrepreneurial activities. Using both primary and secondary data, this article examines the level of income generation, access to resources, market constraints, and the support system available to women entrepreneurs. The findings suggest that while women’s involvement in entrepreneurship has led to better economic self-reliance and empowerment, structural challenges such as lack of financial access, limited mobility, and insufficient policy support persist. The study emphasizes the need for targeted policy interventions, skill development programs, and enhanced institutional support to foster sustainable women entrepreneurship in the region.